Climate Change and Locust Hazard, Causes, Impacts and Probable Solutions - Peroz, Sharifullah; Farhat, Ehsanullah (Journal of Natural Sciences – Kabul University, 2025)
Climate change is a phenomenon that refers to long-term (at least several decades) alterations in the weather and atmospheric conditions of a specific region. In Afghanistan, where approximately 70% of the population relies on agriculture and livestock for their livelihoods, climate change directly and indirectly affects people's subsistence. The objective of this research is to demonstrate how climate change contributes to increased locust infestations, identify the factors promoting these infestations, examine the resulting challenges, and explore potential solutions. The research methodology is qualitative, with data collected through a *systematic review* of secondary sources. The study utilized various scholarly articles, journals, and books, examining 40 academic works. The research findings indicate that climate-induced factors—such as rising temperatures, irregular rainfall, floods, persistent droughts, famine, the decline of locusts' natural predators, and intense winds—have created favorable conditions for locust reproduction and spread. To mitigate this problem, the following recommendations are proposed Raise public awareness* among farmers about climate change and locust-related risks Government institutions* should develop and implement a specialized plan for this.